Coarticulation and Formant Transition Rate in Young Children Who Stutter. - Chang, Soo-eun; Ohde, Ralph N.; Conture, Edward G. (Journal of Speech, Language & Hearing Research, 2002)
The purpose of this study was to assess anticipatory coarticulation and second formant (F2) transition rate (FTR) of speech production in young children who stutter (CWS) and who do not stutter (CWNS). Fourteen CWS and 14 age- and gender-matched CWNS in three age groups (3-, 4-, and 5-year-olds) participated in a picture-naming task that elicited single-word utterances. The initial consonant-vowel (CV) syllables of these utterances, comprising either bilabial {b m} or alveolar {d n s z} consonants and a number of vowels {ı Ι e ε ae u o Đ Đ Đ}, were used for acoustic analysis. To assess coarticulation and speech movement velocity, the F2 onset frequency and F2 vowel target frequency (for coarticulation) and FTR (for speech movement velocity) were computed for each CV syllable and for each participant. Based on these measures, locus equation statistics of slope, y-intercept, and standard error of estimate as well as the FTR were analyzed. Findings revealed a significant main effect for place of articulation and a significantly larger difference in FTR between the two places of articulation for CWNS than for CWS. Findings suggest that the organization of the FTR production for place of articulation may not be as contrastive or refined in CWS as in CWNS, a subtle difficulty in the speed of speech-language production, which may contribute to the disruption of their speech fluency. Reprinted by permission of the publisher.